Dinamika Kepribadian Tokoh Utama dalam Novel Tuhan Izinkan Aku Menjadi Pelacur dan Relevansinya terhadap Psikoanalisis Sigmund Freud - Amelia Zulfiani; Ridha Ahida (AHKAM, 2026)
The study of the dynamics of characters’ personalities in literary works is important for understanding the representation of human inner conflict through the perspective of literary psychology. This research was motivated by the novel Tuhan Izinkan Aku Menjadi Pelacur, which depicts the personality dynamics of the main character, Nidah Kirani, in facing various conflicts throughout her life journey. This study aimed to analyze the personality dynamics of the main character in the novel Tuhan Izinkan Aku Menjadi Pelacur and its relevance to Sigmund Freud’s psychoanalytic theory. This study used a qualitative approach with a library research design. Data were collected through a textual study method by examining the content, meaning, structure, and discourse in the novel, as well as by using a philosophical approach to analyze the character of the main figure. The results showed, first, that the main character experienced personality dynamics throughout the storyline through the impulse of free will as a human being and as a servant demanding justice, reflecting the dominance of the id. However, the ego often emerged as a mediator when the id dominated and confronted the superego, thereby giving rise to actions that conflicted with ethical and moral values. Second, the personality conflict of the main character was relevant to the reality of human life as explained in Sigmund Freud’s psychoanalytic theory, namely that individuals constantly move within the tension among the id, ego, and superego. Thus, this study affirms that the novel Tuhan Izinkan Aku Menjadi Pelacur represents human psychological struggle through the personality conflict of the main character and can be understood as a literary study relevant to Freudian psychoanalysis.